Kaḍapajillā Racayitala Mahāsabhalu, 11, 12 Āgasṭ 1973 : Viśēṣa sañcika (Kaḍapajillā Racayitala Saṅghamu, 1973)
Souvenir brought out in connection with the Cuddapah District Writers Conference; includes articles on Telugu literature and writers from Cuddapah District; includes who's who of Telugu writers from the District.